2011
DOI: 10.1103/physreva.83.033802
|View full text |Cite
|
Sign up to set email alerts
|

Quantum quench influenced by an excited-state phase transition

Abstract: We analyze excited-state quantum phase transitions (ESQPTs) in three schematic (integrable and nonintegrable) models describing a single-mode bosonic field coupled to a collection of atoms. It is shown that the presence of the ESQPT in these models affects the quantum relaxation processes following an abrupt quench in the control parameter. Clear-cut evidence of the ESQPT effects is presented in integrable models, while in a nonintegrable model the evidence is blurred due to chaotic behavior of the system in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
171
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(193 citation statements)
references
References 57 publications
(218 reference statements)
19
171
0
Order By: Relevance
“…Another important feature in the Hamiltonian is the excited-state quantum phase transitions (ESQPT) [31,32], manifested as a singularity in the level density, order parameters, and wave function properties [33,34]. They could have important effects in decoherence [35] and in the temporal evolution for quantum quenches [36]. It is strongly suggested that the relation between the ESQPT and chaos is dependent on the system [37].…”
Section: Arxiv:150905918v1 [Quant-ph] 19 Sep 2015mentioning
confidence: 99%
“…Another important feature in the Hamiltonian is the excited-state quantum phase transitions (ESQPT) [31,32], manifested as a singularity in the level density, order parameters, and wave function properties [33,34]. They could have important effects in decoherence [35] and in the temporal evolution for quantum quenches [36]. It is strongly suggested that the relation between the ESQPT and chaos is dependent on the system [37].…”
Section: Arxiv:150905918v1 [Quant-ph] 19 Sep 2015mentioning
confidence: 99%
“…In this way, we obtain the critical energy in the thermodinamical limit E c /J = −1, which is independent of λ . This critical energy is valid for all λ > λ c and represent the border between two phases with different properties, where the ESQPT's take place, supporting previous results [5]. Properties of this two phases can be explored analyzing the dynamical behavior of certain observables [4].…”
mentioning
confidence: 50%
“…In some collective many-body quantum systems, QPTs are accompanied by ESQPTs, giving rise to a critical energy E c for certain values of the system control parameter [9][10][11][12][13][14][15][16][17]. Traditionally, ESQPTs have been linked to singularities in the density of states or in one of its derivatives, depending on the number of system's degrees of freedom in the semiclassical limit [37].…”
Section: Excited-state Quantum Phase Transitionsmentioning
confidence: 99%
“…They appear in models pertaining to different branches of physics, like the interacting boson model (IBM) [12,13], Lipkin-Meshkov-Glick model [14], vibron model [15], Dicke and Jaynes-Cummings models [10,16,17], kicked top [18], and microwave Dirac billiards [19]. It is worth mentioning that, despite the fact that the excitation energy is linked to the temperature of an isolated system, ESQPTs are qualitatively different from thermal phase transitions.…”
Section: Introductionmentioning
confidence: 99%